PARENTAL SUPPORT, EMOTIONAL INTELLIGENCE, AND ACADEMIC BUOYANCY IN A COLLECTIVISTIC CONTEXT: EVIDENCE FROM INDONESIAN UNIVERSITY STUDENTS - Meilani Rohinsa; Rosida Tiurma Manurung (Universitas Labuhanbatu, 2026)
Purpose- This study aims to examine the mediating role of emotional intelligence in the relationship between parental support and academic buoyancy among university students in a collectivistic context. University students frequently encounter everyday academic challenges that require academic buoyancy. Understanding the psychological mechanisms underlying students’ ability to manage these challenges is essential, particularly in cultural contexts where parental support remains a significant developmental factor.Methodology- This research employed a quantitative, cross-sectional design. The participants were 572 undergraduate students from a private university in Bandung, Indonesia, selected via quota sampling. Data were collected using three instruments: the Academic Buoyancy Scale, the Parents as Social Context Questionnaire, and the Emotional Intelligence Questionnaire. Mediation analysis was conducted using PROCESS Macro Model 4 with a bootstrapping technique involving 5,000 resamples to test the indirect effects.Findings- The results indicated that parental support had a positive and significant effect on emotional intelligence (a = 0.27; p < 0.01), and emotional intelligence positively predicted academic buoyancy (b = 0.87; p < 0.01). Furthermore, the indirect effect of parental support on academic buoyancy through emotional intelligence was significant (Indirect Effect = 0.28; 95% CI [0.14, 0.38]). After including emotional intelligence as a mediator, the direct effect of parental support on academic buoyancy became non-significant, indicating full mediation.Contriution- These findings highlight emotional intelligence as a key mechanism linking parental support to academic buoyancy. The study underscores the role of emotional regulation in academic adaptation, particularly within a collectivistic context